Coulomb interactions in Ga LMIS - Radlicka, Tomás; Lencová, Bohumila (Ultramicroscopy, 2008)
For low emission currents from around 1 microA Ga liquid-metal ion sources (LMIS) produce fine optically bright ion beams that are strongly limited by the Coulomb particle-particle interactions. We present computations of the energy spread, the beam virtual crossover size, and beam brightness based on direct numerical integration of the equation of motion in a numerically calculated field for a number of dimensions of the emission tip. The Coulomb particle-particle interactions are included into the calculation of ion beam evolution. A comparison with experimental data allows to estimate the tip size.